2018
DOI: 10.1037/pst0000189
|View full text |Cite
|
Sign up to set email alerts
|

Countertransference management and effective psychotherapy: Meta-analytic findings.

Abstract: In this article, we review the history and definition of countertransference, as well as empirical research on countertransference, its management, and the relation of both with psychotherapy outcome. Three meta-analyses are presented, as well as studies that illustrate findings from the meta-analyses. The first meta-analysis indicated that countertransference reactions are related inversely and modestly to psychotherapy outcomes (r = −.16, p = .02, 95% CI [−.30, −.03], d = −0.33, k = 14 studies, N = 973). A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
126
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(158 citation statements)
references
References 63 publications
(78 reference statements)
3
126
0
7
Order By: Relevance
“…Therefore, it seems critical for counselors to pay special attention to how they are managing challenging client and relational dynamics. Counselors’ ability to cope with difficulties that arise during the counseling process influences their effectiveness (Hayes, Gelso, Goldberg, & Kivlighan, 2018). Macdonald and Mellor‐Clark (2015) suggested that clinicians who are more aware of the challenges and uncertainty in their work and their professional limitations are better able manage the difficulties that arise in their work with clients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems critical for counselors to pay special attention to how they are managing challenging client and relational dynamics. Counselors’ ability to cope with difficulties that arise during the counseling process influences their effectiveness (Hayes, Gelso, Goldberg, & Kivlighan, 2018). Macdonald and Mellor‐Clark (2015) suggested that clinicians who are more aware of the challenges and uncertainty in their work and their professional limitations are better able manage the difficulties that arise in their work with clients.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for the importance of therapists' interpersonal skills has been derived from research on negative therapy processes (see Binder & Strupp, 1997, for a review) and, more recently, in research on ruptures in the therapeutic alliance . Difficulties in the interpersonal process have been found to be linked with negative therapy outcomes, such as dropout , and to difficulties in therapists' interpersonal behavior (e.g., acting out of countertransference reactions; Hayes, Gelso, Goldberg, & Kivlighan, 2018) or in their internalized relationship models (Steel, Macdonald, & Schroder, 2018). Consequently, developing therapists' interpersonal abilities has been proposed as a priority for psychotherapy training; further, evidence suggests that such trainings are effective Muran, Safran, Eubanks, & Gorman, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…An instrument such as the FWC-12 can also help therapists become more aware of their feelings. Several studies have demonstrated that therapists' feelings are related to patient outcomes (7,20). For therapists to become aware of this phenomenon, it must be given attention.…”
Section: The Fwcmentioning
confidence: 99%
“…Although the concept of CT originally derives from psychoanalytic theory, several current psychotherapeutic approaches regard the therapist's emotional reactions as an important aspect of the therapeutic process (5)(6)(7). However, empirical work on CT has historically been sparse compared to the enormous amount of theoretical literature written about the phenomenon.…”
mentioning
confidence: 99%